PERBANDINGAN KINERJA KEUANGAN ANTAR SUB-SEKTOR PERUSAHAAN CONSUMER NON-CYCLICALS INDONESIA YANG TERDAFTAR DI BURSA EFEK INDONESIA - Novi Diah Wulandari; Regas Panji Pratomo (UPAJIWA DEWANTARA : Jurnal Ekonomi, Bisnis dan Manajemen Daulat Rakyat, 2025)
This study compares financial performance across four sub sectors of Indonesian consumer non cyclical companies listed on the Indonesia Stock Exchange during the 2021 to 2024 post pandemic recovery period. The analysis uses panel data from 26 firms and 104 firm year observations covering Food and Beverage, Pharmaceutical, Tobacco, and Agribusiness companies. The Kruskal Wallis test and Mann Whitney U post hoc comparisons with Bonferroni correction are applied to nine indicators: return on assets, return on equity, net profit margin, current ratio, debt to equity ratio, total asset turnover, cash holding ratio, price to book value, and Tobin’s Q. The results show significant differences in six indicators. Liquidity and leverage produce the largest effect sizes, with pharmaceutical firms recording the highest current ratio and lowest leverage, while Agribusiness firms show the weakest liquidity and relatively high leverage. Food and Beverage firms achieve the highest market valuation, whereas Agribusiness records the lowest Tobin’s Q. Pharmaceutical firms maintain the highest cash reserves, while Tobacco firms hold the lowest. Return on assets does not differ significantly across sub sectors, indicating comparable operational efficiency despite structural financial differences. These findings support investor benchmarking, sector allocation decisions, financial analysis, and sector specific policymaking in Indonesia.